Clinical Comparison of MEBO and Hyaluronic Acid Gel in the Management of Pain after Free Gingival Graft Harvesting: A Randomized Clinical Trial - Ahmed Hassan; Enji Ahmed; Dalia Ghalwash; Azza Ezz Elarab (International Journal of Dentistry)
Aim. This study aimed to compare the effect of MEBO versus 0.2% hyaluronic acid gel (Gengigel®) applied to the palatal donor site on postoperative pain reduction and wound healing after free gingival graft harvesting. Methodology. Thirty-nine patients with different mucogingival defects were included in this study for harvesting a free gingival graft (FGG) for soft tissue augmentation. Patients were randomly assigned into three equal groups: group I (MEBO), group II (0.2% HA Gengigel®), and group III (control). Postoperative pain was recorded by using the Visual Analogue Scale (VAS). Analgesic consumption was recorded for 7 days postoperatively. Wound size was measured at baseline and on days 3, 7, 14, and 21. Postoperative healing of the palatal wound was assessed by the VAS score for color match on days 3, 7, 14, 21, and 42. Results. Results of this study showed significant postoperative pain reduction for the three groups; MEBO showed statistically significant less VAS score compared to the other two groups, while HA showed statistically significant less VAS score compared to the control group. Both MEBO and HA showed statistically significant less total analgesic consumption. No statistically significant difference was observed between groups for wound size. MEBO showed statistically significant higher VAS for color match. Conclusions. Both treatment modalities could reduce postoperative pain following harvesting of FGG and improve the palatal wound healing. However, MEBO showed better outcomes in terms of postoperative pain and color match.